Pengaruh Penambahan Tepung Komposit Umelai (Ubi Jalar, Kacang Merah, Kacang Kedelai) Terhadap Sifat Organoleptik Dan Kandungan Kadar Air Cookies Umelai - indah Paramega; igde Widiada; Abdul Salam; made Darawati (Poltekkes Kemenkes Mataram, 2018)
Background. Food processing products in Indonesia have recently experienced very rapid development. This is due to changes in the lifestyle of people who want to be so fast that food production is also looking for ready-to-eat products but can meet nutritional needs every day. Processed products that are popular with people in Indonesia include: bread, biscuits, noodles, and cookies. Research Methods. Dalam penelitian ini akan dilakukan experiment dengan Rancangan acak Lengkap (RAL) satu faktor yaitu penambahan tepung komposit umelai (tepung ubi jalar, tepung kacang kedelai dan tepung kacang merah) dengan 5 aras perlakuan yaitu t1 20%, t2 30%, t3 40%, t4 50%, t5 60%. Masing–masing perlakuan akan diulang 3 kali sehingga diperoleh 15 (lima belas) unit percobaan. Research Result. Based on the organoleptic test for the parameters of color, odor, taste and texture of soybean cookies with t2 treatment, the addition of 30% composite composite flour was chosen by the panelists as the best treatment. Umelai cookies selected based on organoleptic test ie t2 with the addition of 30% soybean composite flour have a water content of 10.10%, which means that they have not fulfilled the maximum standard of cookies 5% (SNI 01-2973-1992). Conclusion. The addition of soybean composite flour on each treatment t1, t2, t3, t4 and t5 did not significantly influence the organoleptic properties of soybean cookies based on data analysis using the One Way Anova method.